1993
DOI: 10.1002/ijc.2910550311
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of HPV‐16 E6‐E7 transcription in cervical intraepithelial neoplasia by reverse transcriptase polymerase chain reaction

Abstract: Human papillomavirus type 16 (HPV-16) is associated with neoplastic lesions of the uterine cervix. Viral transforming functions have been localized to the E6-E7 open reading frame (ORF) and this ORF is conserved consistently in cervical intraepithelial neoplasia (CIN). Two mRNAs, generated by alternative splicing, are expressed from the E6-E7 ORF. These are known as E6*I and E6*II, and potentially encode the viral E7 and E6 proteins, respectively. It is believed that the HPV-16 transforming ability is mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Total RNA (0.1-1 Ag) was reverse transcribed using an oligo(dT) 17 -primer coupled to a linker sequence p3 (32) and 50 units of Moloney murine leukemia virus reverse transcriptase (SuperScript; Life Technologies) for 1 h at 42jC in a final volume of 20 AL. To control RNA integrity and first-strand cDNA quality, PCR reactions using glyceraldehyde-3-phosphate dehydrogenase-specific primers were performed as described previously (33). First-strand cDNAs encompassing viral oncogene sequences were subsequently amplified by PCR using HPV E7-specific primer [p1] as forward primers (Table 1) and linker p3 as the reverse primer; and 1.5 units of Taq DNA Polymerase (Life Technologies) in a total volume of 50 AL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA (0.1-1 Ag) was reverse transcribed using an oligo(dT) 17 -primer coupled to a linker sequence p3 (32) and 50 units of Moloney murine leukemia virus reverse transcriptase (SuperScript; Life Technologies) for 1 h at 42jC in a final volume of 20 AL. To control RNA integrity and first-strand cDNA quality, PCR reactions using glyceraldehyde-3-phosphate dehydrogenase-specific primers were performed as described previously (33). First-strand cDNAs encompassing viral oncogene sequences were subsequently amplified by PCR using HPV E7-specific primer [p1] as forward primers (Table 1) and linker p3 as the reverse primer; and 1.5 units of Taq DNA Polymerase (Life Technologies) in a total volume of 50 AL.…”
Section: Methodsmentioning
confidence: 99%
“…It is now widely accepted that almost all cervical carcinomas and the majority of vaginal, vulval, penile, and anal cancers arise as consequence of persistent infections with about 13 different HR-HPVs (1). Most of these human papillomavirus (HPV) types show phylogenetic similarities to either HPV16 (31,33,35,52, and 58) or HPV 18 (39,45,59, and 68; ref. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers used to amplify the cyclin D1 gene were the following: dogD1S, 5Ј-CTGGCCATGAACTACCTGGA-3Ј and dogD1AS, 5Ј-GGAAGTGCTCGATGAAGTCG-3Ј. As control, we used the following specific primers to the GAPDH gene (Hsu et al, 1993): primer 1, 5Ј-CATCTCT-GCCCCCTCTGCTGA-3Ј and primer 2, 5Ј-GGATGACCTTGCCCACAGCCT-3Ј.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Commercial nucleic acid sequence-based amplification in a real-time format allows the reliable type-specific detection of E6 and E7 mRNA from HPV types 16, 18, 31, 33, and 45. Several authors have thus suggested that RNA-based assays could be more effective than DNA testing in risk assessment (16,21,22,35,36,38,48,55). In the current study, we test this hypothesis using cytological and histological findings to compare the sensitivities, specificities, positive predictive values (PPVs), and negative predictive values (NPVs) of RNA and DNA testing.…”
mentioning
confidence: 99%